Mastery Learning - A Pedagogy for Leveraging Technology in Teaching NT Greek Grammar - Kime, Harold (HIPHIL Novum, 2015)
This paper describes an implementation of the mastery learning approach in teaching Greek grammar. Tools and techniques designed specifically for mastery learning are described along with methods for formative assessment. The role of the teacher as coach and motivator is clarified as well as methods used to provide corrective feedback. Finally, this paper provides statistical results from a pilot program that demonstrate the effectiveness of the approach .